Efecto del estado fisiológico y del porcentaje de raza Frisona sobre la respuesta reproductiva de ovejas en servicio de primavera - Catalano, R. (2005)
The objective of this study was to evaluate the effect of the physiological status and percentage of Friesian breed on the reproductive performance of ewes after the treatment of oestrus induction. Ewes crosses (Friesian x Corriedale) were divided in 2 groups; Group ORD: 55 ewes in lactating period and Group SECA: 45 ewes in the dry period. The animals were distributed in two subgroups; F50 and F75 (50% and 75% of Friesian breed, respectively). Intravaginal sponges with 60 mg of medroxiprogesterone acetate were used; these devices were withdrawn 12 days later when 500 UI of equine chorionic gonadotrophin were injected. The ewes were mated with rams. Blood samples were taken for the determination of the plasmatic levels of progesterone at the days 6, 11 and 16 after service. The percentages of ewes in estrus and with ovarian reactivation were similar among groups (P>0.05), 82.0% and 96.7%, respectively. The pregnancy rate, fertility and lambing rate were higher in F50 than in F75 (75.0% vs. 49.0%; 78.9% vs. 56.8% y 72.5% vs. 43.1%, respectively, (P<0.05). In conclusion, the pregnancy rate, the fertility and the lambing rate are dependents of the percentage of Friesian breed but independent of the physiological status.